2022
DOI: 10.1002/iid3.732
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0138960 contributes to lipopolysaccharide‐induced periodontal ligament cell dysfunction

Abstract: Background: Periodontitis is a common oral inflammatory disease, and lipopolysaccharide (LPS) is a key risk factor in periodontitis pathology. Here, we used LPS-induced periodontal ligament cells (PDLCs) to explore the molecular mechanism of periodontitis. Methods: Cell viability, proliferation, and apoptosis were analyzed by Cell Counting Kit-8, 5-ethynyl-20-deoxyuridine (EDU), and flow cytometry assays, respectively. Apart from that, their targeting relationship was validated using dual-luciferase reporter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Previous studies have revealed that some circRNAs such as circ_0138960 and circ_0081572 are involved in LPS‐induced dysfunction of PDLCs 17,18 . Our work reported the involvement of another novel circRNA circ_0087199 in LPS‐induced injury of PDLCs for the first time.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies have revealed that some circRNAs such as circ_0138960 and circ_0081572 are involved in LPS‐induced dysfunction of PDLCs 17,18 . Our work reported the involvement of another novel circRNA circ_0087199 in LPS‐induced injury of PDLCs for the first time.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have revealed that some circRNAs such as circ_0138960 and circ_0081572 are involved in LPS-induced dysfunction of PDLCs. 17,18 Our work reported the involvement of another novel circRNA circ_0087199 in LPS-induced injury of PDLCs for the first time. Our data showed that circ_0087199 expression was upregulated in periodontal ligament tissues of periodontitis patients, which are consistent with previous results.…”
Section: Discussionmentioning
confidence: 85%